Pengaruh Penggunaan Limbah Plastik LDPE Terhadap Karakteristik Laston AC-WC Dengan Metode Marshall: The Influence of LDPE Plastic Waste Utilization on the Characteristics of AC-WC Mixture Using the Marshall Method - Iqbal, Iqbal; Sukowati, Dwi Guntoro; Rusmin, Muhammad; Desembardi, Faried; Sasim, Kartika Putri (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2024)
LDPE plastic waste a common type of plastic waste found in Sorong, SouthwestPapua Province. The primary cause is the widespread use of LDPE as a packaging material for everyday products. The use of LDPE plastic waste an additive in Asphalt Concrete Wearing Course (AC-WC) offers several benefits, such as improving asphalt concrete quality, speeding up the production process, and minimizing environmental impact. This study aims to identify the characteristics of AC-WC mixtures with and without the addition of LDPE plastic waste based on Marshall Standard parameters. The research used a laboratory experimental method, which included several stages such as testing the physical properties of aggregate and asphalt, determining the optimum asphalt content, and testing to measure Marshall parameters by adding LDPE plastic at 2.5%, 5%, and 7% of asphalt weight. The results showed that the optimum bitument content (OBC) for the AC-WC mixture is 6.5%. Based on the Marshall test focused on mechanical properties, the addition of 5% LDPE plastic to the AC-WC mixture yielded the highest stability value of 1824.54 kg. As for volumetric properties, the addition of LDPE plastic increased the VIM and VMA values. Conclusion, adding LDPE plastic waste can enhance the performance of the AC-WC mixture.